IMPLEMENTATION OF THE PENTAHELIX SYNERGY MOVEMENT PROGRAM FOR THE OPTIMIZATION OF DISASTER MANAGEMENT IN NORTH SUMATRA PROVINCE (A CASE STUDY IN ASAHAN REGENCY) - Robert Efendi Purba; Adam Adam; Beby Masitho Batubara (Universitas KH. Abdul Chalim Mojokerto, 2026)
Asahan Regency is one of the regions in North Sumatra Province that has a relatively high level of disaster vulnerability, particularly hydrometeorological disasters such as floods, tornadoes, and landslides. The complexity of disaster risks requires a disaster management model that does not rely solely on the government but involves various actors in a collaborative manner. In line with the Pentahelix approach developed by Ranga and Etzkowitz (2013) and the concept of collaborative governance by Ansell and Gash (2008), the Government of North Sumatra Province has developed the Pentahelix Synergy Movement Program (SIGAP) as a cross-sectoral collaboration model in disaster management. This study aims to analyze the implementation of the SIGAP Program in Asahan Regency with a focus on collaboration between the local government and the business sector as the main actors in the initial stage of the application of the Pentahelix.This research uses a qualitative method with a descriptive approach through interview, observation, and documentation techniques. The results of the study show that collaboration between the government and the business sector in the SIGAP Program has made a tangible contribution to improving disaster management capacity, particularly in terms of funding, provision of logistics, and the acceleration of emergency response. The local government acts as the coordinator and controller of policy, while the business sector provides support through corporate social responsibility programs and operational partnerships. However, the implementation of SIGAP has not yet been optimal due to weak collaborative institutions, the absence of strong partnership regulations, limitations in the integrated disaster data system, and the low level of structured involvement of academics, communities, and the media.